THE iAPPLICATION iOF iTHE iPROBLEM iBASED iLEARNING iTO iTHE iLEARNING iOUTCOMES iOF iJUNIOR iHIGH iSCHOOL iSTUDENT - murtiana pohan; Khairil Arif (Pendidikan IPA, FMIPA, UNP, 2023)
The ilearning ioutcomes iof istudents iat iSMP iin iscience isubjects ihave inot ireached ithe iMinimum iCompleteness iCriteria i(KKM). iThe imethod iused ito iovercome ithese iproblems iis iby iapplying ithe iProblem iBased iLearning i(PBL) imodel. iThis istudy iaims ito idetermine iwhether ithe i(PBL) imodel ihas ian ieffect ion istudent ioutcomes iin ithe imaterial iof iadditives iand iaddictive isubstances iat iSMPN. iThis itype iof iresearch iis iQuasi iExperiment. iThe iresearch idesign iused iwas ithe iNon iEquivalent iControl iGroup iDesign. iThe isampling itechnique iis iPurposive iSampling. iThe isample ias ithe ieperimental iclass iis iVIII.A iusing ithe iPBL imodel iwhile ithe isample ias ithe icontrol iclass iis iVIII.B iusing ithe idirect ilearning imodel. iThe iresearch iinstrument iwas ia iwritten itest, inamely imultiple ichoice iquestions. iData iwere ianalyzed iusing ithe iNormality iTest, iHomogeneity iTest, iT-Test iand iN-Gain iTest. iThe iresult iof ithe icalculation iof ithe iT-Test iis ithat ithe ivalue iof itcount i= i4.736308 iand ithe ivalue iof ittable i= i2.019541, itcount ithat i> ittable, ithus iH0 iis irejected iand iH1 iis iaccepted. iThe iconclusion iof ithe iresearch iis ithat ithere iis ian ieffect iof ithe iPBL ilearning imodel ion ithe ilearning ioutcomes iof iclass iVIII istudents iin ithe imaterial iof iadditives iand iaddictive isubstances iat iSMP. Keywords: iPBL, iAdditif iAnd iAddictive, i iLearning iOutcomes